Jabatan Kerja Raya Ipoh, Perak Darul Ridzuan / Muhammad Zairul Bardan ... [et al.] - Maarof, Muhammad Badri; Hashim, Muhammad Hazman; Rusli, Muhammad Fareez Razzey; Suhaidi, Zaidatul Izzanie; Zulkefli, Nur Ashikin (2015)
JKR Ipoh building is owned by Kementerian Kerja Raya Malaysia. It is located in Jalan Panglima Bukit Gantang Wahab, Ipoh, Perak Darul Ridzuan. The construction was started on 2nd June 1981 and finished on 8th September 1983. The building was operated on 6th October 1983. The overall cost of building is around RM25.4 billion. The height of building is 27.6 metre with 2614.220 m² of gross floor area. JKR Ipoh building have 240 staffs and it’s functioning as one of the government building to give a service to the all people in this country especially in managing the asset and project. We had identified of maintenance organizational chart in JKR Ipoh Building. From the organizational chart, they know their roles and duties. They are using in-house maintenance for the minor works and calling out-source maintenance for any major problems. JKR Mechanical Department maintain the services in JKR Ipoh Building such as lift services, air conditioner and fire-fighting system while for the out-source, they open the tender to all the contractor out there such as pest control and housekeeping services. Facilities in the building, elevation view, description logo of the building, adjacent building are described clearly with information referred to the JKR Ipoh building. All the information that we get from this building has divided into some chapter which is detail information of the building, maintenance organization, maintenance policy, building design and technology, maintenance strategy, legal aspect, financial aspect and problem and recommendation. From this case study, we have gain knowledge about the management of the building, especially about the maintenance management. All data and information about this building has been collected and compile it as a final project report.